TOPORS-mediated RAD51 SUMOylation facilitates homologous recombination repair. Issue 3 (21st January 2022) - Hariharasudhan, Gurusamy; Jeong, Seo-Yeon; Kim, Min-Ji; Jung, Sung Mi; Seo, Gwanwoo; Moon, Ju-Ran; Lee, Sumi; Chang, In-Youb; Kee, Younghoon; You, Ho Jin; Lee, Jung-Hee
Abstract: Homologous recombination (HR) is critical for error-free repair of DNA double-strand breaks. Chromatin loading of RAD51, a key protein that mediates the recombination, is a crucial step in the execution of the HR repair. Here, we present evidence that SUMOylation of RAD51 is crucial for the RAD51 recruitment to chromatin and HR repair. We found that topoisomerase 1-binding arginine/serine-rich protein (TOPORS) induces the SUMOylation of RAD51 at lysine residues 57 and 70 in response to DNA damaging agents. The SUMOylation was facilitated by an ATM-induced phosphorylation of TOPORS at threonine 515 upon DNA damage. Knockdown of TOPORS or expression of SUMOylation-deficient RAD51 mutants caused reduction in supporting normal RAD51 functions during the HR repair, suggesting the physiological importance of the modification. We found that the SUMOylation-deficient RAD51 reduces the association with its crucial binding partner BRCA2, explaining its deficiency in supporting the HR repair. These findings altogether demonstrate a crucial role for TOPORS-mediated RAD51 SUMOylation in promoting HR repair and genomic maintenance.